Development of E-Module Problem Based Learning Models on Temperature and Heat Physics Materials - Sari, Nadya Endah; Yurnetti, Yurnetti (PILLAR OF PHYSICS EDUCATION, 2023)
The 2013 curriculum requires students to have 4C skills, namely: creative thinking, critical thinking and problem solving, communication and collaboration. Physics problem solving skills, especially temperature and heat materials are still low, so a model of problem based learning is needed to increase these skills. To support the process of learning, materials of teaching in consist  of modules are needed. Along with the use of technology, e- modules are made so that students are more interested and enthusiastic to take part in learning. This research purpose to find out how the validity of the product of making e-module physics material is temperature and heat. This research includes development research with the plomp model. This limited research stage to the expert review stage. The first stage, namely preliminary research, obtained initial data in the form of an analysis of student needs from several journals and an analysis of the KD 3.4 curriculum on temperature and heat material. The second stage is an expert review, the e-module is validated by 5 validators. The data collection instrument in the research was a validation questionnaire. The data analysis in the research used the Aiken's V index. The validation data analysis result obtained that the PBL physics e-module model on temperature and heat material was very valid. The validity test sheet consists of three assessment components. The first component is the material and language aspects with an average value of 0.88 in categories was very valid. The second component is the characteristics of the e-module with an average value of 0.90 in category was very valid. The third component is the PBL model with an average value of 0.86 in category was valid. So, the average result of these three components is 0.88 in the very valid category. From the validation results, it is concluded that the PBL model e-physics module on temperature and heat material is valid.